Effects Of Porosity On Mechanical Properties Of Metal Matrix Composite: An Overview - Aqida, S. N.; Ghazali, M. I.; Hashim, J. (Penerbit UTM Press, 2004)
Porosity in cast metal matrix composite (MMC) has been known as a defect affecting the enhancement of strength, particularly in particle-reinforced MMC. From previous reviews, among the causes of porosity formation are air bubbles entering the melt matrix material, water vapour on the particles surfaces, gas entrapment during mixing process, evolution of hydrogen, and shrinkage during solidification. Many studies had revealed that casting parameters are the main factors affecting porosity formation. Optimum properties of cast MMC are attained with least porosity content. Generally, increasing content of porosity will decrease the mechanical properties of MMC such as tensile strength, Young’s modulus, Poisson ratio, and damping capacity. The presence of porosity decreased the mechanical properties of cast MMC as the failure process is initiated from the voids formed.